2019
DOI: 10.5194/bg-16-2481-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pedogenic and microbial interrelation in initial soils under semiarid climate on James Ross Island, Antarctic Peninsula region

Abstract: Abstract. James Ross Island (JRI) offers the exceptional opportunity to study microbial-driven pedogenesis without the influence of vascular plants or faunal activities (e.g., penguin rookeries). In this study, two soil profiles from JRI (one at Santa Martha Cove – SMC, and another at Brandy Bay – BB) were investigated, in order to gain information about the initial state of soil formation and its interplay with prokaryotic activity, by combining pedological, geochemical and microbiological methods. The soil p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 100 publications
3
18
0
Order By: Relevance
“…other Antarctic habitats (e.g. Ganzert et al, 2011;Yan et al, 2017;Meier et al, 2019). Differences between the sites with regards to the observed community compositions were found only in near-surface substrates in the upper 10 cm, while the microbial communities became less diverse and more similar with increasing depth across all investigated soil profiles.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…other Antarctic habitats (e.g. Ganzert et al, 2011;Yan et al, 2017;Meier et al, 2019). Differences between the sites with regards to the observed community compositions were found only in near-surface substrates in the upper 10 cm, while the microbial communities became less diverse and more similar with increasing depth across all investigated soil profiles.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, changes in soil microstructure, induced e.g. by frequent freeze-thaw cycles and associated changes in pore spacing and nutrient contents have been related to shifts in microbial community compositions in soils from maritime Antarctica (Meier et al, 2019). Meier et al (2019) observed a change towards a lenticular microstructure below 20 cm depth, which was related to significant changes in the microbial community compositions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations